2005
DOI: 10.1111/j.1349-7006.2005.00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of immunoglobulin superfamily 11 (IGSF11) as a novel target for cancer immunotherapy of gastrointestinal and hepatocellular carcinomas

Abstract: We previously performed gene expression profile analyses of 20 intestinal-type gastric cancers, and identified a set of genes whose expression levels were elevated in cancer tissues compared to their corresponding non-cancerous tissues. In the present study we focused on the immunoglobulin superfamily 11 gene (IGSF11). Its expression was also elevated in colorectal cancers and hepatocellular carcinomas as well as intestinal-type gastric cancers. Northern blot analysis showed that it was expressed abundantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 43 publications
1
50
0
Order By: Relevance
“…We have also shown that immunoglobulin superfamily 11 is a novel TAA that is expressed in gastric, colorectal and liver cancers, and reported antigenic epitope peptides for immunotherapy. (34) In this study, we have shown that SCRN1 is frequently expressed in gastric cancer and colon cancer tissues. Northern blot analysis also showed that expression of this gene is abundant in testis and ovary but barely detectable in other normal adult tissues examined.…”
Section: Discussionmentioning
confidence: 71%
“…We have also shown that immunoglobulin superfamily 11 is a novel TAA that is expressed in gastric, colorectal and liver cancers, and reported antigenic epitope peptides for immunotherapy. (34) In this study, we have shown that SCRN1 is frequently expressed in gastric cancer and colon cancer tissues. Northern blot analysis also showed that expression of this gene is abundant in testis and ovary but barely detectable in other normal adult tissues examined.…”
Section: Discussionmentioning
confidence: 71%
“…Kdr, which is also called Vefgr2, is a receptor for Vegfa (34), and can be targeted to prevent VEGF signaling and suppress angiogenesis required for malignant tumor growth (21). Antisera directed against IGSF11 can also be used to prevent tumor cell invasion and metastasis (22).…”
Section: Discussionmentioning
confidence: 99%
“…For example, inhibitors have been generated to target kinase insert domain receptor (Kdr) to prevent VEGF signaling and suppress angiogenesis required for malignant tumor growth (21). Immunological reagents have also been targeted to immunoglobulin superfamily 11 (IGSF11) (22) and Pdpn (23) to prevent tumor cell invasion and metastasis. …”
Section: Identification Of Genes Affected By Src and Contactmentioning
confidence: 99%
“…We confirmed herein its expression in testis and brain but showed that IGSF11 is also expressed in adrenal gland. This gene is up-regulated in gastrointestinal and hepatocellular carcinomas, encodes a receptor essential for gastric cancer cell growth (34,35), and has been described as a novel immunogenic target since a natural HLA-A2-restricted T cell epitope was identified and a subsequent anchor-modified peptide was synthesized (35). TMEFF1 and TMEFF2, for transmembrane protein with EGF-like and two follistatin-like domains 1 and 2, respectively, encode putative growth factors predominantly expressed in the brain (36,37).…”
Section: Discussionmentioning
confidence: 99%